Rebel eaudiobook Starbuck chronicles series, book 1. - Cornwell, Bernard (The Starbuck Chronicles, 2011)
This bestselling author is highly praised by both critics and fans for his action-packed historical novels. Casts of colorful characters spring to life in battle scenes vivid with authentic military detail. When William Faulconer rescues Nate Starbuck, his son's friend, from the clutches of a Yankee-hating mob in Virginia, he finds a grateful and willing recruit for Faulconer's Legion. But Nate's decision to fight against his native North is only one of the human dilemmas facing the Legion. The Legion commander's son is against the war, and his daughter's fiance is plotting for control of the family fortune. As a motley gathering of men prepares to engage the enemy at Bull Run, they have high hopes of ending the war before it starts. No one can foresee the changes in store for themselves and for their country. Nate Starbuck and his compatriots leap from the book in full battle regalia with Ed Sala's narrative magic. Action scenes are all the more exciting because listeners identify with the well-drawn characters and understand the circumstances that lead them to this historical moment.